Efeitos do hormônio do crescimento sobre vias de sinalização intracelular na miopatia associada à insuficiência cardíaca de ratos - Lima, Aline Regina Ruiz [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Although chronic heart failure is usually associated with skeletal muscle atrophy, physiopathological mechanisms involved in muscle mass loss are not completed established. Growth hormone (GH) has anabolic effects. However, its effects on skeletal muscle preservation during catabolic diseases are not well understood. GH stimulates IGF-1, which activates PI3K/Akt pathway to inhibit atrogin-1 and MuRF-1. GH can also modulate myogenic regulatory factors and myostatin and follistatin protein expression as well as satellite cells activation. In this study, we evaluated the effects of GH administration on trophicity and intracellular signaling pathways involved in the atrophy process in peripheral skeletal muscles of rats with aortic stenosis (AS)-induced heart failure. After heart failure detection, GH was administered for 14 days (AS-GH group). Results were compared with those from Sham and non-treatment AS groups. Transthoracic echocardiogram was performed before and after treatment. Trophicity was analyzed in soleus and white portion of gastrocnemius muscles. Protein expression was evaluated by Western blot and satellite cells activation by immunofluorescence. Statistical analyses: ANOVA and Tukey or Kruskal-Wallis and Student-Newman- Keuls. Before treatment, AS groups presented similar echocardiographic parameters. GH attenuated systolic dysfunction. Sectional fiber areas of gastrocnemius did not differ between groups; in soleus, they were lower in both AS groups than Sham. In gastrocnemius, MRF4 and atrogin-1 were higher in AS and AS-GH groups. GH treatment attenuated MyoD increase. Immunofluorescence showed that staining with anti-neural cell adhesion molecule (NCAM) and antineonatal myosin heavy chain isoform were statistically more intense in AS-GH than AS and Sham. In soleus, GH activated IGF-1 and PI3K proteins. NCAM immunofluorescence was increased in both AS groups. In conclusion, GH treatment attenuates left ...

A insuficiência cardíaca (IC) crônica é comumente associada a atrofia de músculos esqueléticos, cujos mecanismos responsáveis ainda não estão completamente esclarecidos. O hormônio do crescimento (GH) tem efeitos anabólicos. Entretanto, seus efeitos na preservação da massa muscular em doenças catabólicas ainda não são bem entendidos. O GH estimula o IGF-1 e ativa a via PI3K/Akt inibindo seus efetores atrogina-1 e MuRF-1. Além disso, pode modular a expressão dos fatores de regulação miogênica e das proteínas miostatina e folistatina e a função de células satélites. O objetivo deste estudo é avaliar os efeitos da administração do GH sobre o trofismo e vias de sinalização intracelular envolvidas no processo de atrofia de músculos esqueléticos periféricos de ratos com insuficiência cardíaca crônica induzida por estenose aórtica (EAo). Após detecção clínica de IC, o GH foi administrado por 14 dias (grupo EAo-GH). Os resultados foram comparados com aqueles de grupos Sham e EAo sem tratamento. Ecocardiograma foi realizado antes e após o tratamento. O trofismo foi analisado nos músculos esqueléticos sóleo e porção branca do gastrocnêmio. A expressão proteica foi avaliada por Western blot e a ativação de células satélites por imunofluorescência. Análise estatística: ANOVA e Tukey ou Kruskal-Wallis e Student-Newman-Keuls. Antes do tratamento, os grupos EAo apresentaram comportamento semelhante em relação às variáveis ecocardiográficas. O tratamento com GH atenuou a disfunção sistólica. A área seccional das fibras do gastrocnêmio não diferiu entre os grupos e a do sóleo foi menor nos grupos com estenose aórtica que no Sham. No gastrocnêmio, MRF4 e atrogina-1 foram aumentadas nos grupos EAo e EAo-GH. O tratamento com GH atenuou elevação da MyoD e aumentou a visualização das proteínas NCAM e isoforma neonatal da cadeia pesada de miosina. No sóleo, o GH ativou as proteínas ...
Keywords: Insuficiencia cardiaca; Somatotropina; Sistema musculoesquelético; Atrofia muscular; Massa muscular; Músculos - Doenças; Muscles - Diseases